Analysis of link interruption characteristics in the DTN - LI Yun; WANG Xiao-ying; LIU Zhan-jun; ZHOU Ya-hui (Tongxin xuebao)
The characteristic of wireless link in the DTN has an important influence on the performance of networks. The deterministic and opportunistic events can lead to the link interruption in the DTN. The connection of wireless links was analyzed when deterministic interruption events exist. By finding common recovery time of two-node, the rules was got- ten that connectivity characteristic of the wireless networks with changes over time.